Adsorbate-induced curvature and stiffening of graphene - Svatek, S.; Scott, O.; Rivett, J.; Wright, Kathleen; Baldoni, M.; Bichoutskaia, E.; Taniguchi, T.; Watanabe, K.; Marsden, A.; Wilson, N.; Beton, P. (2015)
© 2014 American Chemical Society. The adsorption of the alkane tetratetracontane (TTC, C44H90) on graphene induces the formation of a curved surface stabilized by a gain in adsorption energy. This effect arises from a curvature-dependent variation of a moiré pattern due to the mismatch of the carbon-carbon separation in the adsorbed molecule and the period of graphene. The effect is observed when graphene is transferred onto a deformable substrate, which in our case is the interface between water layers adsorbed on mica and an organic solvent, but is not observed on more rigid substrates such as boron nitride. Our results show that molecular adsorption can be influenced by substrate curvature, provide an example of two-dimensional molecular self-assembly on a soft, responsive interface, and demonstrate that the mechanical properties of graphene may be modified by molecular adsorption, which is of relevance to nanomechanical systems, electronics, and membrane technology.